2022
DOI: 10.3390/nano12060969
|View full text |Cite
|
Sign up to set email alerts
|

Surface Transformation of Spin-on-Carbon Film via Forming Carbon Iron Complex for Remarkably Enhanced Polishing Rate

Abstract: To scale down semiconductor devices to a size less than the design rule of 10 nm, lithography using a carbon polymer hard-mask was applied, e.g., spin-on-carbon (SOC) film. Spin coating of the SOC film produces a high surface topography induced by pattern density, requiring chemical–mechanical planarization (CMP) for removing such high surface topography. To achieve a relatively high polishing rate of the SOC film surface, the CMP principally requires a carbon–carbon (C-C) bond breakage on the SOC film surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In particular, it was confirmed that the dependencies of the Si wafer polishing rate on the CMP head and CMP platen rotation speeds as well as polishing time presented a typical Preston behavior, indicating that the Si wafer CMP slurry including a hydrolysis reaction accelerator with amine functional group would prefer to be a mechanically dominant CMP, as shown in Figure S3 . Note that the Si wafer polishing rate was determined on the basis of both chemical and mechanical properties [ 18 , 19 , 20 , 22 , 26 , 47 , 48 , 49 , 50 , 51 , 52 ]. In addition, the Si wafer CMP slurry using the hydrolysis reaction accelerator with amine functional group (i.e., EDA) evidently presented a remarkably high Si wafer polishing rate at a relatively low rotation speed (i.e., 70 rpm), a low head pressure (i.e., 4 psi), and a softer pad, as shown in Table S2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, it was confirmed that the dependencies of the Si wafer polishing rate on the CMP head and CMP platen rotation speeds as well as polishing time presented a typical Preston behavior, indicating that the Si wafer CMP slurry including a hydrolysis reaction accelerator with amine functional group would prefer to be a mechanically dominant CMP, as shown in Figure S3 . Note that the Si wafer polishing rate was determined on the basis of both chemical and mechanical properties [ 18 , 19 , 20 , 22 , 26 , 47 , 48 , 49 , 50 , 51 , 52 ]. In addition, the Si wafer CMP slurry using the hydrolysis reaction accelerator with amine functional group (i.e., EDA) evidently presented a remarkably high Si wafer polishing rate at a relatively low rotation speed (i.e., 70 rpm), a low head pressure (i.e., 4 psi), and a softer pad, as shown in Table S2 .…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the zeta-potential decrease in both the colloidal silica abrasives and the polished Si wafer surface due to coating EDA on them reduced significantly the repulsive force between the colloidal silica abrasives and the polished Si wafer surface via Coulombic interaction between abrasives and film surface (i.e., , where , , , and are the repulsive force between the colloidal silica abrasives and the polished Si wafer surface, the zeta-potential of the colloidal silica abrasives, the zeta-potential of the polished Si wafer, and distance between the colloidal silica abrasives and the polished Si wafer surface, respectively), as shown in Figure 4 c [ 46 , 47 , 48 , 49 , 50 ]. To understand how the relative electrostatic repulsive force influences the Si wafer polishing rate, the correlation was determined between the Si wafer polishing rate and relative electrostatic repulsive force for NaOH, KOH, and EDA, as shown in Figure 4 d. For all of the hydrolysis reaction accelerators, the Si wafer polishing rate decreased notably, from 552.8 to 139.5 nm/min, when the relative electrostatic repulsive force was increased from 1043 to 1503 abs., i.e., higher relative electrostatic repulsive force led to lower Si wafer polishing rate [ 48 , 49 , 50 , 51 , 52 ]. In particular, the relative electrostatic repulsive force (i.e., 1503 abs.)…”
Section: Resultsmentioning
confidence: 99%